2011
DOI: 10.1126/scisignal.2001518
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of K-Ras Enhances Activation and Facilitates Binding to Select Downstream Effectors

Abstract: GTP-loaded Ras induces multiple signaling pathways by binding to its numerous effectors such as Raf and PI3K. Ras activity can be influenced by activation of Ras-GEFs that stimulate GDP release and GTP loading or by inhibition of Ras-GAPs that stimulate GTP hydrolysis. Here, we report that monoubiquitination of Lys147 within the G domain of wild-type K-Ras, the Ras gene most frequently mutated in cancer, leads to enhanced GTP loading. Furthermore, ubiquitination increases the ability of the oncogenic Gly-12-Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
191
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 30 publications
7
191
1
1
Order By: Relevance
“…Additionally, several lysines within the core G domain of RAS undergo post-translational modifications, including acetylation, ubiquitylation, and methylation (5), but the role of these distinct modifications in regulating RAS function is still unclear. For example, KRAS monoubiquitylation at lysine 147 up-regulates RAS activity, signaling, and tumorigenesis (6). Additionally, lysine 104 has been shown to be a minor site of ubiquitylation, and we have previously shown that ubiquitylation of KRAS at this position does not alter the intrinsic biochemical properties or regulation by GEFs and GAPs (7).…”
mentioning
confidence: 99%
“…Additionally, several lysines within the core G domain of RAS undergo post-translational modifications, including acetylation, ubiquitylation, and methylation (5), but the role of these distinct modifications in regulating RAS function is still unclear. For example, KRAS monoubiquitylation at lysine 147 up-regulates RAS activity, signaling, and tumorigenesis (6). Additionally, lysine 104 has been shown to be a minor site of ubiquitylation, and we have previously shown that ubiquitylation of KRAS at this position does not alter the intrinsic biochemical properties or regulation by GEFs and GAPs (7).…”
mentioning
confidence: 99%
“…Although no function has yet been assigned to monoubiquitination of Rac1, it is possible that this modification is involved in the mechanism by which Rho interacts with downstream effectors. Monoubiquitination of mammalian Ras proteins can lead to cell transformation (71) and does so by promoting nucleotide exchange or by impeding the binding of the GTPase activating protein (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…2010), whereas monoubiquitylation of K‐Ras at K104 or K147 by an unknown E3 ligase does not affect its intracellular localization but rather promotes the binding and activation of the downstream effector proteins RAF and phosphoinositide 3‐kinase by an unknown mechanism (Sasaki et al . 2011). …”
Section: Regulation Of Membrane‐associated Processes By Monoubiquitylmentioning
confidence: 99%